PENERAPAN DISCOVERY LEARNING BERBANTUAN MEDIA BOLA, BALON, DAN TTS UNTUK MENINGKATKAN AKTIVITAS BELAJAR PESERTA DIDIK - Inca Pritonasya Milaningsih; Eny Winaryati; Dwi Anggraeni Ristanti (LitbangMu Jawa Tengah and Teacher Professional Education UNIMUS, 2024)
This study aims to improve the learning activities of Class XI-5 students at SMA Negeri 15 Semarang in chemistry lessons by implementing the discovery learning model assisted by teaching aids (balls and balloons) and crossword puzzle (TTS) media. Initial observations identified several issues, including low student activity levels, averaging only 37.22%, lack of enthusiasm during lessons, and minimal attention during group presentations. Additionally, the teacher faced time constraints in providing in-depth explanations, making it challenging for students to understand abstract chemistry concepts. This study employed the Classroom Action Research (CAR) method using the Kemmis and McTaggart model, consisting of four main components: planning, action, observation, and reflection. In Cycle I, the use of teaching aids and media in the discovery learning model effectively increased activity to 50.48%, though it did not meet the target. Improvements were implemented in Cycle II with more interactive learning methods, such as crossword puzzles, which increased the average activity level to 87.71%, surpassing the success criterion of 80%.